Impact of thermal barrier coating application on the combustion, performance and emissions of a diesel engine fueled with waste cooking oil biodiesel-diesel blends - SAYIN, CENK (ELSEVIER SCI LTD, 2014)
Biodiesel fuel was produced from waste cooking oil by transesterification process. B20 and B50 blends of biodiesel-petroleum diesel were prepared. These blends and D2 fuels were tested in a single cylinder CI engine. Performance, combustion and emission values of the engine running with the mentioned fuels were recorded. Then the piston and both exhaust and intake valves of the test engine were coated with layers of ceramic materials. The mentioned parts were coated with 100 mu m of NiCrAl as lining layer. Later the same parts were coated with 400 mu m material of coating that was the mixture of 88% of ZrO2, 4% of MgO and 8% of Al2O3. After the engine coating process, the same fuels were tested in the coated engine at the same operation condition. Finally, the same engine out parameters were obtained and compared with those of uncoated engine parameters in order to find out how this modification would change the combustion, performance and emission parameters. Results showed that the modification of the engine with coating process resulted in better performance, especially in considerably lower brake specific fuel consumption (Bsfc) values. Besides, emissions of the engine were lowered both through coating process and biodiesel usage excluding the nitrogen oxides (NOx) emission. In addition, the results of the coated engine are better than the uncoated one in terms of cylinder gas pressure, heat release rate (HRR) and heat release (HR). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Combustion; Thermal barrier coating; Diesel engine; Biodiesel; EXHAUST EMISSIONS; OXIDATION